A spatiotemporally resolved atlas of mRNA decay in the C. elegans embryo reveals differential regulation of mRNA stability across stages and cell types - Peng, Felicia; Nordgren, C. Erik; Murray, John Isaac

(untitled) (Genome Research, 2024)
During embryonic development, cells undergo dynamic changes in gene expression that are required for appropriate cell fate specification. Although both transcription and mRNA degradation contribute to gene expression dynamics, patterns of mRNA decay are less well understood. Here, we directly measure spatiotemporally resolved mRNA decay rates transcriptome-wide throughout C. elegans embryogenesis by transcription inhibition followed by bulk and single-cell RNA sequencing. This allows us to calculate mRNA half-lives within specific cell types and developmental stages, and identify differentially regulated mRNA decay throughout embryonic development. We identify transcript features that are correlated with mRNA stability and find that mRNA decay rates are associated with distinct peaks in gene expression over time. Moreover, we provide evidence that, on average, mRNA is more stable in the germline than in the soma and in later embryonic stages than in earlier stages. This work suggests that differential mRNA decay across cell states and time helps to shape developmental gene expression, and it provides a valuable resource for studies of mRNA turnover regulatory mechanisms.